Multimedia Services in Intelligent Environments Integrated Systems - Tsihrintzis, George A.; Virvou, Maria (Smart Innovation, Systems and Technologies, 2010)
This book is a continuation of our previous books on multimedia services in intelligent environments [1-4]. It includes fourteen chapters on integrated multimedia systems and services covering various aspects such as geographical information systems, recommenders, interactive entertainment, e-learning, medical diagnosis, telemonitoring, attention management, e-welfare and brain-computer interfaces. Each chapter in the book was reviewed by two independent reviewers for novelty and clarity of the research presented in it.